2002
DOI: 10.1177/875687050202100402
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Preparation and Service Delivery Issues in Rural Areas: The State of the Art

Abstract: Preparation of high quality personnel to provide educational services to students with disabilities living in rural areas is, at best, challenging. Findings from a comprehensive study concerning the status of the implementation of the Individuals with Disabilities Education Act (IDEA) in rural settings and the issues such implementation presents to teacher education programs in these areas are discussed. Members of the American Council on Rural Special Education (ACRES) participated in the study. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 9 publications
(8 reference statements)
1
30
0
Order By: Relevance
“…National research studies suggest that a primary obstacle to retaining teachers is isolation-both geographic and social (Hammer et al, 2005;Provasnik et al, 2009;Schwartzbeck & Prince, 2003). One promising, evidence-based strategy for increasing special education teacher retention in rural areas is professional development via online technology (Sundeen & Wienke, 2009;Williams, Martin, & Hess, 2002).…”
mentioning
confidence: 99%
“…National research studies suggest that a primary obstacle to retaining teachers is isolation-both geographic and social (Hammer et al, 2005;Provasnik et al, 2009;Schwartzbeck & Prince, 2003). One promising, evidence-based strategy for increasing special education teacher retention in rural areas is professional development via online technology (Sundeen & Wienke, 2009;Williams, Martin, & Hess, 2002).…”
mentioning
confidence: 99%
“…Two trends emerged from the literature, as contributors to the predicted shortage of special education teachers and TVIs (Ludlow et al, 2005;Summer et al, 2006 and individualized education services and affects the quality of instruction (Summer et al, 2006). Of the literature reviewed (Berry, Petrin, Gravelle, & Farmer, 2011;Billingsley et al, 2009;Carlson, Brauen, Klein, Schroll, & Willig, 2002;Piwowar, Thiel, & Ophardt, 2013;Sindelar, Brownell, & Billingsley, 2010) (Kluwin, Morris, & Clifford, 2004;Pogrund & Wibbenmeyer, 2008;Seitz, 1994;Swenson, 1995;Williams & Warren, 2007;Williams, Martin, & Hess, 2010). Pogrund and Wibbenmeyer (2008) described the significance of the TVI's role as follows:…”
Section: Significance Of Teacher Efficacymentioning
confidence: 99%
“…The literature review suggested that novice itinerant TVIs lack opportunities for professional development that is specific to their field of special education and often have limited to no access to a veteran TVI (Griffin-Shirley et al, 2004;Seitz, 1994;Williams et al, 2010). Billingsley et al (2009) reinforced the importance of targeted professional development and stated: "these experiences (i.e., content specific to their field of teaching) were perceived as more helpful than generic efforts aimed at professional development of all beginning teachers" (p. 28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are opting to participate in distance versus traditional campus-based courses for a variety of reasons, such as the lack of geographic proximity to university classrooms and fmancial or family obligations that preclude attendance in traditional campus-based programs (Braun, 2008;Riffell & Sibley, 2004;Yudko, Hirokawa, & Chi, 2008). Increasing the pool of potential new teachers by providing access for all ' qualified applicants to special education teacher training programs via distance education programs is particularly pertinent in light of nation-wide shortages of special education teachers (Katsiyannis, Zhang, & Conroy, 2003), especially in rural areas (Menlove &c Lignugaris/Kraft, 2004;Sundeen & W^ienke, 2009;Williams, Martin, & Hess, 2002). I Distance teacher preparation programs have become an increasingly popular and effective vehicle for preparing highly qualifidd special education teachers in rural areas (Brownell, Bishop, & Sindelar, 2005;Ludlow & Brannon, 1999;Spooner, F. Spooner, Algozzine, & Jordan, 1998).…”
mentioning
confidence: 99%